The benefits of a hospital palliative care team. (2nd July 2019) - Sganga, Federica; Barillaro, Christian; Tamburrano, Andrea; Nicolotti, Nicola; Cambieri, Andrea; Bernabei, Roberto; Turriziani, Adriana
Abstract : Aim: To investigate the association between a hospital palliative care unit assessment and hospital outcome. Methods: This was a prospective cohort study. Data were assessed from all patients treated and followed by the hospital palliative care team (HPCT) from November 2016 until December 2017. Results: The mean age of the 588 patients was 73.15±13.6 years. All of the patients included in the study were referred to palliative care. A large proportion of patients were affected by cancer, 69.7% (410), while 30.3% (178) were affected by an advanced chronic illness. The three most frequent cancers were: gastrointestinal (n=81, 19.8%), gynaecological (n=66, 16.1%) and lung (n=63, 15.4%); the three most frequent chronic advanced diseases were: advanced dementia (n=45, 25.3%), severe ischaemic/haemorrhagic stroke (n=36, 20.2%) and severe heart failure (n=25, 15.3%). The majority of patients were in clinical wards (n=476, 81.0%) and the average length of stay was 22.9 days. Hospital outcome trends were evaluated in terms of length of stay and number of deaths that occurred in the hospital. In particular, length of stay decreased from 25.8 days to 18.1 days, hospital death from 13 to 0 during the time that the HPCT assessed patients for an appropriate discharge. Conclusion: The HPCT is an effective means of managing patients affected by severe illness, reducing the number of deaths that occur within the hospital, long periods of hospitalisation and instances of readmission. However, further studies are required to fully assess the impact of an HPCT on hospital outcomes.